Transformasi Mayarakat Petani Sejahtera di Desa Bontojai Kecamatan Bontocani Kabupaten Bone - Andi Sulfajar; Andi Agustang; Moh Thamrin Mappalahere (Phinisi Integration Review, 2022)
The purpose of this study is to describe and analyze the driving factors for the transformation and transformation of farming communities to achieve prosperity in Bontojai Village, Bontocani District, Bone Regency. This qualitative research uses a phenomenological study strategy. Data was collected by means of participant observation, in-depth interviews and documentation. The validity of the data using the persistence of observations, triangulation of sources and detailed descriptions. The data analysis techniques used were: making small notes, grouping data, analyzing, presenting data and drawing conclusions.The results of the study show (1) The driving factors for the transformation are the behavior of hard work and persistence to maximize the agricultural land owned. Government assistance, educated farmers and experience of nomads who educate the community as a form of counseling through discussions or stories so as to facilitate the adoption of technology that can support agriculture. There is technological innovation and the use of fertilizers and pesticides. (2) the transformation of farming communities to achieve prosperity is to abandon traditional farming methods, to plant long, medium and short term crops. In addition, they do not depend entirely on agricultural products (having other income).